PENGARUH PENGGUNAAN LEMBAR KERJA MAHASISWA (LKM) BERBASIS MASALAH MELALUI GOOGLE CLASSROOM TERHADAP HASIL BELAJAR MAHASISWA PADA MATERI FISIOLOGI TUMBUHAN - sukmawati syam; Nur Muhajirah Yunus (Jurnal Biogenerasi, 2021)
This study aims to determine the effect of using problem-based student worksheets taught through google classroom on Plant Physiology material. This research is an experimental study (pre-experimental) with a one group pretest posttest design. The subjects of this study were students of Biology Education, semester VI as many as 19 students. The research instrument was in the form of student learning outcomes tests. Data collection techniques were carried out by tests, observations and documentation. The data analysis technique used paired t-test. The results showed that there was a significant effect of using problem-based student worksheets through google classroom on student learning outcomes on plant physiology material.